2019
DOI: 10.1186/s40425-019-0619-8
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage repair gene mutations and their association with tumor immune regulatory gene expression in muscle invasive bladder cancer subtypes

Abstract: Background Molecular subtyping of urothelial cancer (UC) has significantly advanced the understanding of bladder tumor heterogeneity and development of prognostic and predictive biomarkers. Evolving evidence across cancers strongly suggests that tumor immunoediting has a profound impact on the behaviour of cancer cells and their adaptation to the co-evolving microenvironment and response to treatment. In alignment with these concepts, recent immune checkpoint blockade (ICB) therapies in UC have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 50 publications
3
62
2
Order By: Relevance
“…DDR mutations were also associated with the activation of IL6‐JAK‐STAT3 pathway. One previous study has shown that DDR deficiency did not exhibit a significantly higher level of immune cells in bladder cancer . Similarly, we did not identify a significantly higher level of abundance in 22 immune cell types calculated by CIBERSORT.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…DDR mutations were also associated with the activation of IL6‐JAK‐STAT3 pathway. One previous study has shown that DDR deficiency did not exhibit a significantly higher level of immune cells in bladder cancer . Similarly, we did not identify a significantly higher level of abundance in 22 immune cell types calculated by CIBERSORT.…”
Section: Discussioncontrasting
confidence: 75%
“…One previous study has shown that DDR deficiency did not exhibit a significantly higher level of immune cells in bladder cancer. 21 Similarly, we did not identify a significantly higher level of abundance in 22 immune cell types calculated by CIBERSORT. Paradoxically, an increased Th1 cell level was observed in OvCa with DDR mutation, which indicated an immunologically hot state.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations